Development of a novel salivary gland cancer lymph node staging system. Issue 15 (9th May 2018) - Aro, Katri; Ho, Allen S.; Luu, Michael; Kim, Sungjin; Tighiouart, Mourad; Clair, Jon Mallen‐St.; Yoshida, Emi J.; Shiao, Stephen L.; Leivo, Ilmo; Zumsteg, Zachary S.
Abstract : BACKGROUND: Current lymph node (LN) staging for salivary gland cancer (SGC) is extrapolated from mucosal head and neck squamous cell carcinoma. However, given its unique biology and clinical behavior, it is possible that a SGC‐specific LN staging system would be more accurate. METHODS: Patients from the National Cancer Data Base with nonmetastatic SGC of the head and neck who were diagnosed from 2004 through 2013 and underwent surgical resection and neck dissection removing at least 10 LNs were included. Multivariable models were constructed to assess the association between survival and LN factors, including number of metastatic LNs, extranodal extension, LN size, and lower LN involvement. RESULTS: Overall, 4520 patients met the inclusion criteria. An increasing number of metastatic LNs was found to be strongly associated with worse survival without plateau. The risk of death increased more rapidly up to 4 LNs (hazard ratio, 1.34; 95% confidence interval, 1.27‐1.41 [ P < .001]), and was more gradual for additional LNs >4 (hazard ratio, 1.02; 95% confidence interval, 1.01‐1.03 [ P < .001]). LN size, extranodal extension, and lower LN involvement appeared to have no impact on survival when accounting for the number of metastatic LNs. Recursive partitioning analysis was used to create a novel SGC LN staging system in which N0 indicates 0 positive LNs, N1 indicates 1 to 2 positive LNs, N2 indicates 3 to 21 positive LNs, and N3 indicates ≥ 22 positive LNs. This system exhibited greater concordance than the current American Joint Committee on Cancer (eighth edition) system. CONCLUSIONS: Quantitative LN burden is an important determinant of survival in patients with SGC. Use of this variable may improve SGC staging. Cancer 2018. © 2018 American Cancer Society . Abstract : Lymph node classification for salivary gland cancer historically has been extrapolated from head and neck squamous cell carcinoma, which is a biologically distinct disease. Herein, using regression and recursive partitioning analysis, the authors demonstrate that the number of positive lymph nodes can be used to create a lymph node classification for salivary gland cancer that outperforms the current American Joint Committee on Cancer eighth edition staging system.